PENGARUH GREEN MARKETING TOOL’S TERHADAP PERILAKU PEMBELIAN KONSUMEN PADA PRODUK LAMPU PHILIPS LED - Wibawa, I Made Satria Putra; Warmika, I Gde Ketut (E-Jurnal Manajemen, 2019)
The purpose of this study was to determine the effect of green marketing Tool's on consumer buying behavior. This research was conducted on Philips LED lighting products in Denpasar. The number of samples chosen was 112 people, with purposive sampling method. Data collection was done through questionnaire, with data analysis technique used is multiple liniear regression. The results of this study show that the tool of green marketing tool that consists of eco-label, eco-brand, and environmental advertisement have a positive and significant effect on consumer purchasing behavior. This shows that consumers who realize the importance of environmentally friendly products can encourage the decision to purchase a product.